In situ Chromatin Interaction Analysis Using Paired‐End Tag Sequencing. Issue 8 (5th August 2021) - Wang, Ping; Feng, Yuliang; Zhu, Kun; Chai, Haoxi; Chang, Ya‐ting; Yang, Xiaofei; Liu, Xiyuan; Shen, Chen; Gega, Eva; Lee, Byoungkoo; Kim, Minji; Ruan, Xiaoan; et al.
Abstract: Chromatin Interaction Analysis Using Paired‐End Tag Sequencing (ChIA‐PET) is an established method to map protein‐mediated chromatin interactions. A limitation, however, is that it requires a hundred million cells per experiment, which hampers its broad application in biomedical research, particularly in studies in which it is impractical to obtain a large number of cells from rare samples. To reduce the required input cell number while retaining high data quality, we developed an in situ ChIA‐PET protocol, which requires as few as 1 million cells. Here, we describe detailed step‐by‐step procedures for performing in situ ChIA‐PET from cultured cells, including both an experimental protocol for sample preparation and data generation and a computational protocol for data processing and visualization using the ChIA‐PIPE pipeline. As the protocol significantly simplifies the experimental procedure, reduces ligation noise, and decreases the required input of cells compared to previous versions of ChIA‐PET protocols, it can be applied to generate high‐resolution chromatin contact maps mediated by various protein factors for a wide range of human and mouse primary cells. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Sample preparation and data generation Support Protocol : Bridge linker preparation Basic Protocol 2 : Data processing and visualization